Salidroside protects against ventilation-induced lung injury by inhibiting the expression of matrix metalloproteinase-9 - Hui Zhang; Wenwen Dong; Siyuan Li; Yunqian Zhang; Zhou Lv; Lu Yang; Lai Jiang; Tao Wu; Yan Wang (Taylor & Francis Group, 2021)
Context Salidroside, a compound extracted from Rhodiola rosea L. (Crassulaceae), possesses many beneficial pathological effects. Objective To explore the effect of salidroside on ventilator-induced lung endothelial dysfunction in vivo and in vitro. Materials and methods In vivo, male ICR mice were divided into sham, ventilation, salidroside, and ventilation plus salidroside groups. The mice were ventilated for 4 h, salidroside (50 mg/kg) was administrated intraperitoneally before ventilation, dexamethasone (Dex) (5 mg/kg) was used as a positive control. In vitro, mouse lung vascular endothelial cells (MLVECs) were treated with salidroside, MMP-9 siRNA, and BAY11-7082 (10 μM), and then exposed to cyclic stretch for 4 h. Afterward, lung tissues and MLVECs were collected for further analysis. Results Salidroside pre-treatment significantly reversed the expression of vascular endothelial cadherin (VE-cadherin) and zonula occluden-1 (ZO-1) proteins in cyclic stretch-treated MLVECs (0.46 ± 0.09 vs. 0.80 ± 0.14, 0.49 ± 0.05 vs. 0.88 ± 0.08) and ventilated lung tissues (0.56 ± 0.06 vs. 0.83 ± 0.46, 0.49 ± 0.08 vs. 0.80 ± 0.12). The results further indicated that salidroside inhibited the expression of matrix metalloproteinase-9 (MMP-9), whereas knockdown of its expression restored the expression levels of VE-cadherin (0.37 ± 0.08 vs. 0.85 ± 0.74) and ZO-1 (0.48 ± 0.08 vs. 0.81 ± 0.11) in stretched MLVECs. Meanwhile, salidroside inhibited the NF-κB signalling pathway and alleviated lung injury. Conclusions Salidroside protected against stretch-induced endothelial barrier function, improving lung injury after ventilation. Thus, salidroside may be a promising therapeutic agent for patients with MV-induced lung injury.